6. If cos*x + cos2x + cos²3x = 1 th...
Question
Fullscreen

6. If cos*x + cos2x + cos²3x = 1 then - (A) X = (2n + 1), nel (B) x = (2n +1, ne I

JEE/Engineering Exams
Maths
Solution
91
Rating
4.0 (1 ratings)
Fullscreen
( cos ^{wedge} 2 x+cos wedge 2(2 x)+cos wedge 2(3 x)=1 ) ( (1+cos 2 x) / 2+(1+cos 4 x) / 2+cos ^{wedge} 2(3 x)=1 ) ( 1+cos 2 x+1+cos 4 x+2 cos wedge 2(3 x)=2 ) ( 2+cos 2 x+cos 4 x+2 cos wedge 2(3 x)=2 ) ( cos 2 x+cos 4 x+2 cos wedge 2(3 x)=0 ) ( 2 cos ((4 x+2 x) / 2) cos ((4 x-2 x) / 2)+2 cos wedge 2(3 x)=0 ) ( cos 3 x cos x+cos wedge 2(3 x)=0 ) ( cos 3 x(cos 3 x+cos x)=0 ) ( cos 3 x=0, therefore 3 x=p i / 2+-2 k p i,(3 p i) / 2+-2 k p i, x=p i / 6+-2 / 3 k p i, p i / 2+-2 / 3 k p i ) ( cos 3 x+cos x=0 ) ( cos 3 x=-cos x ) ( 3 x=p i+x+-2 k p i, x 2 x=(1+-2 k) p i, x=p i / 2(1+-2 k) ) ( 3 x=p i-x+-2 k p i, quad: 4 x=(1+-2 k) p i, quad x=p i / 4(1+-2 k) )
Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free